Improvement in Hematology Interprofessional Care: Simulation With an Emphasis on Collaboration - Zachary Liederman; Brandon Tse; Calum Slapnicar; Kristen Daly; Christine Leger; Jessica Petrucci; Douglas Campbell; Martina Trinkaus (Association of American Medical Colleges, 2020)
Introduction For many training programs, including hematology, there are limited structured opportunities to practice collaboration as a competency. Training is often limited to ad hoc interactions during clinical rotations. Accordingly, there is further need for immersive and standardized collaboration educational programs. This pilot study explored simulation for developing and assessing collaboration competency among hematology residents. Methods Two standardized simulation center scenarios were developed that required residents to work in interprofessional teams. The objectives were to develop collaboration competence and confidence through experiential learning and facilitated reflection. Team members included education and simulation experts as well as hematology nurses as embedded participants. Case 1 presented a 72-year-old male with stage 4 lymphoma experiencing shortness of breath during a rituximab infusion. Case 2 presented a 68-year-old male who suffered a provoked pulmonary embolism. Both cases utilized a simulated clinic space. Pre, post, and 3-month questionnaires (self-assessed collaboration competency and simulation evaluation) were completed. Each session included structured debriefing with facilitated reflection focused on collaboration. Results Seven senior hematology subspecialty residents participated. Despite residents entering the simulation cases with confidence in collaboration, higher collaboration confidence ratings were observed on postsimulation questionnaires (8.2 vs. 7.6 on a 10-point Likert scale). Residents demonstrated awareness of appropriate collaboration skills, but at times failed to implement knowledge into action. Facilitated reflection during the debrief helped residents critique their collaboration performance and develop improvement plans. Discussion Simulation is a promising tool for teaching and assessing collaboration within hematology training.